DOES RELIGIOSITY AFFECT THE INTENTION TO PURCHASE HALAL FAST FOOD FROM NON-MUSLIM COUNTRIES OF ORIGIN? - Gunawan, Arie Indra; Gaffar, Vanessa (Universitas Airlangga, 2021)
This paper aims to increase knowledge about the buying intention of halal fast food products. This study examines the influence of the country of origin of halal fast-food providers on purchase intentions. This study also measures the role of religiosity in mediating the relationship between country of origin and purchase intention of halal fast food. This knowledge will be very meaningful because the condition of Indonesia is the largest halal ecosystem, but in the fast-food category, it is dominated by providers from non-Muslim foreign countries. This research is a descriptive study, questionnaires were distributed randomly online via social media, finally getting 245 data from millennial Muslim consumers who could become research respondents. SEM-PLS with the help of statistical software WarpPLS 7.0 is used to explain the research model. This study shows that country of origin affects the purchase intention of halal fast food products, besides this research shows that religiosity is able to moderate country of origin towards the purchase intention of halal fast food. The results of this study reinforce the assumption that country of origin has a significant effect on purchase intention. Especially in fast food products, millennial consumers in Indonesia show that they already have a point of view and perception about the country of origin of halal fast food in Indonesia. Another finding in the study is that religiosity influences the purchase intention of halal fast-food, and has a moderating effect on the country of origin on purchase intention.